Pig feed additive for effectively increasing digestion rate of nitrogen and phosphorus - WU ZHIQING; ZHU CHANGSHENG; LI SHICHUAN (2017)
The invention discloses a pig feed additive for effectively increasing digestion rates of nitrogen and phosphorus, and belongs to the field of feed additives. The pig feed additive consists of a yucca smalliana preparation, ginger, dried tangerine or orange peel, arginine, taurine, glycine betaine, fructooligosaccharide, chitosan oligosaccharide and a carrier, wherein the carrier is wheat bran and medical stone. By adopting the pig feed additive, the digestion and the absorption of nitrogen and phosphorus in daily feed by pigs can be effectively improved, emission of nitrogen and phosphorus in manure can be reduced, environment pollution can be reduced, meanwhile the content of fat and delicate flavor substances of muscle can be increased, and a function of improving the quality of pig meat can be achieved. 本发明公开了种有效提高氮磷消化率的猪用饲料添加剂，属于饲料添加剂领域。该添加剂由丝兰制备物，生姜，陈皮，精氨酸，牛磺酸，甜菜碱，果寡糖，壳寡糖及载体组成，载体为麦麸和麦饭石。本添加剂能有效提高猪对日粮中氮磷的消化吸收，减少粪中氮磷的排放，降低对环境的污染，同时还具有能提高肌肉脂肪含量和鲜味物质，改善猪肉品质的作用。